Smart Schools : The Future of Education Through Internet of Things (IoT) Integration - Hassan Faisal Zaman; Ahmed Raza (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
The Internet of Things (IoT) is transforming the education sector by connecting devices, environments, and people to improve learning experiences. This paper investigates the integration of IoT technologies in schools, such as smart classrooms, connected learning tools, and automated systems for student tracking. The study highlights how IoT enhances the learning environment, improves operational efficiency, and provides real-time feedback for both students and teachers.